A New Flexible Graphite Composite Electrical Grounding Material - Huang, Tao; Hu, Yuanchao; Xie, Hongping; Du, Changqing; An, Yunzhu; Shen, Wentao; Liu, Zhixiang; Cheng, Meng (Frontiers in Materials, 2022)
Corrosion has been an inevitable problem of metallic grounding grids. To propose an effective method avoiding the above corrosion, a new type of nonmetallic grounding material was made in this paper. It is called flexible graphite composite grounding material, namely FGCGM for short. It is made by high-purity flake graphite with Litz hierarchical structure. And a series of experiments have been carried out to verify its feasibility as electrical grounding material, including material resistivity and its contact resistance measurement, temperature tolerance test, mechanical performance test and scaled electrical grounding test of several typical electrical grounding grids. These experimental results all indicate that characteristics of the new flexible graphite composite grounding material can well meet practical electrical engineering requirements.